Optimization of mixed-strain fermentation process of apple Jiaosu - ZHANG Haiyan, KANG Sanjiang, GOU Lina, YUAN Jing, ZENG Chaozhen, MU Yuwen, SONG Juan (Zhongguo niangzao)
In this experiment, the apple Jiaosu was fermented with Cyberlindnera fabianii, Saccharomyces cerevisiae, Lactiplantibacillus pentosus, and Leuconostoc mesenteroides as fermentation strains. The effects of different strain combination fermentation on soluble solid, pH, total acid, reducing power, superoxide dismutase (SOD) activity and sensory score of apple Jiaosu were studied, and the process for yeast fermentation stage and lactic acid bacteria fermentation stage of apple Jiaosu were optimized by single factor test and response surface method. The results showed that the optimal process conditions of yeast fermentation stage of apple Jiaosu with multi-strain fermentation were as follows: C. fabianii ∶ S. cerevisiae 1∶0.20, inoculum 3.3%, fermentation temperature 23 ℃ and initial pH 4.70. The optimal process conditions of lactic acid bacteria fermentation stage were as follows: L. pentosus ∶ L. mesenteroides 1∶1, inoculum 5.2%, fermentation temperature 33 ℃ and initial pH 5.1. Under the optimized conditions, the sensory scores, SOD activity, total acid content, reducing power, soluble solid content, and pH of apple Jiaosu fermented by multiple strains were 9.82, 55.83 U/ml, 4.96 g/L, 6.83, 3.14 °Bx, and 2.96, respectively. This study provided a theoretical basis for the industrial production of apple Jiaosu products.